2022
DOI: 10.1155/2022/6919130
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Comprehensive Nursing Intervention Combined with WeChat Platform Propaganda and Education of ERAS Concept on Postoperative Functional Recovery of Patients with Gallbladder Polyps

Abstract: To analyze the effect of comprehensive nursing intervention based on ERAS’s concept in laparoscopic gallbladder polyp (GP) surgery on patients’ postoperative quality of life and nursing job satisfaction. Ninety patients with polyps were included in this article until October 2021. In this format, the 45 cases are divided into governing bodies and committees according to their processing time. As recommended by the ERAS committee, the committee provides daily and patient care, as well as training on the WeChat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The routine nursing is more basic nursing for patients during the hospital treatment, and the long-term follow-up of patients is not timely. 8 In the medical field, the Internet can convey knowledge more intuitively, simply and vividly, which is convenient for patients to use, help improve the level of patient learning, and promote communication between doctors and patients. 9 Continuing care typically includes discharge planning, home guidance, and follow-up check-ups.…”
Section: Introductionmentioning
confidence: 99%
“…The routine nursing is more basic nursing for patients during the hospital treatment, and the long-term follow-up of patients is not timely. 8 In the medical field, the Internet can convey knowledge more intuitively, simply and vividly, which is convenient for patients to use, help improve the level of patient learning, and promote communication between doctors and patients. 9 Continuing care typically includes discharge planning, home guidance, and follow-up check-ups.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%